PENGGUNAAN METODE SPECTRAL FITTING UNTUK MENDETERMINASI OPERATOR ATENUASI AKIBAT KANDUNGAN FLUIDA DI LAPANGAN PANAS BUMI - Mia Uswatun Hasanah; Andri Dian Nugraha; Muhammad Rahmat Sule (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
Attenuation is the physical parameters of rock that can reflect the subsurface geological conditions. We conducted attenuation tomographic imaging in the geothermal field by using the Microearthquake (MEQ) data in the form of attenuation operator, t*. We applied a method of spectral fitting to invert for the t* value.. Keywords: Please write 3-5 keywords in english with font 9 point, italic.